Entrepreneurial Financing Strategies and Growth of Women-Led SMEs in Makassar - Umar, Nurfakhriyah (Generasi Sains Indonesia, 2025)
Women-led small and medium enterprises (SMEs) have emerged as vital contributors to economic growth and social empowerment in Makassar. Despite their increasing presence, many face persistent financial and structural barriers that hinder expansion and sustainability. This study investigates the relationship between entrepreneurial financing strategies and the growth of women-led SMEs in Makassar. Using a mixed-method approach, quantitative data were collected from 150 women entrepreneurs through structured surveys, complemented by qualitative interviews and focus group discussions. The quantitative analysis examined key financing sources, including personal savings, microfinance, bank loans, and informal borrowing, while business growth was measured through revenue, market reach, and employment indicators. Data were analyzed using descriptive statistics, correlation, and regression models, supported by qualitative insights into financial access challenges and strategic decision-making. The results indicate that personal savings remain the dominant financing source (38%), followed by microfinance (25%), bank loans (20%), and informal borrowing (17%). Regression analysis confirmed that formal financing particularly bank loans and microfinance positively influences revenue and market expansion. However, qualitative findings reveal enduring barriers such as collateral constraints, high interest rates, and limited financial literacy. The study concludes that improving access to affordable credit and entrepreneurial capacity-building is essential to strengthen women-led SME growth in Makassar.